1988
DOI: 10.1111/j.1432-1033.1988.tb13800.x
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor‐induced biosynthesis of psoralens in Ammi majus L. suspension cultures

Abstract: Suspension cultures of Ammi majus L. cells produce various linear furanocoumarins in response to treatment with elicitor preparations from either Alternaria carthami Chowdhury or Phytophthora megasperma f.sp. glycinea. Microsomes which were isolated from these cells 14 h after addition of the elicitor eficiently catalyzed the conversion of demethyl[3 -''C]suberosin into labelled (+)marmesin in the presence of NADPH and oxygen. In contrast to the chemical cyclization of demethylsuberosin by rn-chloroperoxybenzo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 36 publications
4
57
0
Order By: Relevance
“…5). Overall, the data demonstrated that CYP71AJ1 encodes psoralen synthase, which is probably too labile for detection in isolated yeast microsomes, in accordance with previous observations on A. majus microsomes (36,42). The activity might be stabilized by adjustment of the N-terminal anchor sequence.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…5). Overall, the data demonstrated that CYP71AJ1 encodes psoralen synthase, which is probably too labile for detection in isolated yeast microsomes, in accordance with previous observations on A. majus microsomes (36,42). The activity might be stabilized by adjustment of the N-terminal anchor sequence.…”
Section: Resultssupporting
confidence: 78%
“…Three consecutive cytochrome P450-dependent reactions converting demethylsuberosin to bergaptol (Fig. 1) and identified in Ammi microsomes (35,36) provided the basis for the differential cloning approach, which fully confirmed the previous proposal of separate CYP entities (31,35,36). Psoralen synthase represents the first cloned coumarin-committed monooxygenase, and CYP71AJ1 gives access to a new CYP71 subfamily of enzymes.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations